Estudio integrado del golfo de Guayaquil del mioceno al reciente - Cobos Mite, Luis Emilio (2010)
This study integrates biostratigraphic information, well logs and seismic sections available in the Gulf of Guayaquil. Sequence boundaries, systems tracts, faults and structures major were determined. Was concluded that the Gulf of Guayaquil is not a traditional pull-apart basin; this is a pull-apart basin in transtensive regime and with a ductile detachment zone, were depocentres developed near the basin boundary faults, separated by intra-basin structural highs that are the transfer zones of transcurrent movement. The opening began in the Middle Miocene. Analyzing the source rock age, the oil expulsion time, periods of structure´s formation, and the verified presence of oil and gas; was determined that the structures formed in the late Miocene or earlier are the more favorable to be effective reservoir.